Disturbances in local and systemic immunity in children with atopic dermatitis - William M. Archer, Oliver S. Mackenzie, Dawson J. Payne (Academic Journal of Clinicians, 2024)
Recently, a steady increase in allergic diseases has been observed. About 30-40% of the world's population suffers from allergies. Of particular concern is the increase in allergy among children, as well as severe manifestations, atypical forms of allergic diseases that are difficult to treat with traditional therapy. It has been proven that atopic dermatitis (AD) is common among young children. The development of allergic inflammation in AD is associated with an imbalance of lymphocytes, mediators of intercellular interaction. Currently, in the pathogenesis of AD, a special place is given to the immune system, indicators of cellular, humoral, local immunity, as well as pro- and anti-inflammatory cytokines. It is cytokines - mediators of intercellular interaction that play a certain role in regulating the immune response in AD. Analysis of publications shows that insufficient attention is paid to the study of the state of local immunity of the skin, the relationship of humoral and cellular immunity with local immunity. To date, these issues remain open. A total of 105 patients (55 boys and 50 girls) with AD were observed in the pulmonology department of the Republican Children's Clinical Hospital of the Ministry of Health of the Republic of North Ossetia - Alania. The observation was carried out from 2016 to 2019. Patients were divided into two groups: IgE-associated and non-IgE-associated. The patients were assessed for clinical and immunological laboratory parameters, as well as local and systemic immunity.